Revealing the dynamics of ultraphytoplankton diversity in cihu lake by integrated hplc and molecular sequencing analyses (Bangladesh Journal of Botany, 2026)
Eutrophication is a major ecological issue in freshwater lakes. Ultraphytoplankton, with small cell sizes and high sensitivity, are effective indicators for water trophic status assessment. In this study, a two-year ecological survey was conducted in Cihu Lake, a shallow urban lake in the middle Yangtze River, using HPLC-CHEMTAX and 16S rDNA high-throughput sequencing to explore ultraphytoplankton community diversity and its environmental drivers. Results showed Cihu Lake shifted from lightly eutrophic (2022) to moderately eutrophic (2023), with its trophic state significantly affected by Dissolved Oxygen, Potassium Permanganate Index, Total Phosphorus, Ammonium Nitrogen (N-NH₄⁺), Secchi Depth, and Chlorophyll a. Nitrogen limitation occurred in the first three seasons of 2022 and throughout 2023, while nitrogen-phosphorus co-limitation occurred in winter 2022. Fucoxanthin, Alloxanthin, Zeaxanthin, and Chlorophyll b were major photosynthetic pigments while Euglenophyta, Cryptophyta, Cyanophyta, and Chrysophyta were dominant phytoplankton, indicating distinct seasonal succession regulated by Total Phosphorus, Secchi Depth, and Water Temperature. Meanwhile, dominant bacterial phyla included Proteobacteria, Bacteroidota, Cyanobacteria, Actinobacteriota, and Verrucomicrobiota, with Phosphate (PO43-), Potassium Permanganate Index, and Chlorophyll a as key influencing factors, and most phytoplankton taxa were negatively correlated with bacterial communities.Bangladesh J. Bot. 55(1): 21-30, 2026 (March)